Application of holography and augmented reality based technology to visualize the internal structure of the dental root – a proof of concept - Damian Dolega-Dolegowski; Klaudia Proniewska; Magdalena Dolega-Dolegowska; Agnieszka Pregowska; Justyna Hajto-Bryk; Mariusz Trojak; Jakub Chmiel; Piotr Walecki; Piotr S. Fudalej (Head & Face Medicine, 2022)
Abstract Background The Augmented Reality (AR) blends digital information with the real world. Thanks to cameras, sensors, and displays it can supplement the physical world with holographic images. Nowadays, the applications of AR range from navigated surgery to vehicle navigation. Development The purpose of this feasibility study was to develop an AR holographic system implementing Vertucci’s classification of dental root morphology to facilitate the study of tooth anatomy. It was tailored to run on the AR HoloLens 2 (Microsoft) glasses. The 3D tooth models were created in Autodesk Maya and exported to Unity software. The holograms of dental roots can be projected in a natural setting of the dental office. The application allowed to display 3D objects in such a way that they could be rotated, zoomed in/out, and penetrated. The advantage of the proposed approach was that students could learn a 3D internal anatomy of the teeth without environmental visual restrictions. Conclusions It is feasible to visualize internal dental root anatomy with AR holographic system. AR holograms seem to be attractive adjunct for learning of root anatomy.